2016
DOI: 10.1038/jp.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Home visits by community health workers to improve identification of serious illness and care seeking in newborns and young infants from low- and middle-income countries

Abstract: The objectives of this review were to evaluate the effect of home visits by trained community health workers (CHWs) to successfully identify newborns and young infants (up to 59 days of age) with serious illness and improve care seeking from a health facility. The authors searched the Cochrane Central Register of Controlled Trials, MEDLINE and EMBASE. Abstracts of all articles were read by two authors independently and relevant articles selected. Data were extracted in a pretested questionnaire by two authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Our analysis has demonstrated that caregivers who received visits from the BRAC's CHWs before 1 year of the survey had received information about the MNP product and its provision to children in their everyday foods. We did not find a similar study in the literature although there is evidence that home visits by CHWs are an effective intervention to improve infants' and young children's health (23,24) and maternal health (25) . Previous *Z-test (P values <0·05 were regarded as statistically significant).…”
Section: Discussionmentioning
confidence: 54%
“…Our analysis has demonstrated that caregivers who received visits from the BRAC's CHWs before 1 year of the survey had received information about the MNP product and its provision to children in their everyday foods. We did not find a similar study in the literature although there is evidence that home visits by CHWs are an effective intervention to improve infants' and young children's health (23,24) and maternal health (25) . Previous *Z-test (P values <0·05 were regarded as statistically significant).…”
Section: Discussionmentioning
confidence: 54%
“…This emphasizes the limited number of health workers available in the health care system, as reported by closely related studies which outcomes also reported similar shortage of health workers in their surveys [11,12,13]. Allison et al [14] outcomes further support health care workers visitation to increase positive health outcomes as the neonatal mortality rate of 7.1 per 1000 live births was recorded among population studied for one year compared to the National value of 38 per 1000 live births while Tripathi et al [15] reported "quality evidence that home visits by trained community health workers are associated with improved care-seeking for ill young infants to health facilities in resource-limited settings".…”
Section: Discussionmentioning
confidence: 55%
“…of community health workers (CHW)/volunteers: This is a very important component of primary care system and has been successful in many settings [20][21][22][23]. In some countries they are fully recognised and paid by the government [24] and this is what it should be. However in some countries they are just volunteers.…”
Section: Utilisationmentioning
confidence: 99%